2018
DOI: 10.1007/s10067-017-3973-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of renal and patient outcomes in a Spanish cohort of patients with ANCA-associated vasculitis and renal involvement

Abstract: The classification of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) remains controversial. The main objective of this study was to define the respective values of ANCA serotype-based classification, clinicopathological classification, and histopathological classification in predicting patient and renal outcomes in a Spanish cohort of patients with ANCA with specificity for myeloperoxidase, MPO-ANCA, versus ANCA with specificity for proteinase 3, PR3-ANCA. Two hundred and forty-five pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
5
8
0
Order By: Relevance
“…The focal class, containing ≥50% of normal glomeruli, has the best renal survival, while the sclerotic class, containing ≥50% of global sclerotic glomeruli, has the worst renal survival among the categories. These results have been reproduced in other clinical studies [19, 21]. In this study, the renal survival of the focal class was 100% during our observation period, which was the best survival rate.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The focal class, containing ≥50% of normal glomeruli, has the best renal survival, while the sclerotic class, containing ≥50% of global sclerotic glomeruli, has the worst renal survival among the categories. These results have been reproduced in other clinical studies [19, 21]. In this study, the renal survival of the focal class was 100% during our observation period, which was the best survival rate.…”
Section: Discussionsupporting
confidence: 88%
“…In 2010, a renal histopathological classification of AAG in European patients was proposed, and the four general categories (focal, crescentic, mixed, and sclerotic) significantly correspond to renal survival [18]. This histological classification has been validated for various ethnic groups and countries, and its usefulness has been established [1921]. Concerning renal prognosis, the focal class has good prognosis, while the sclerotic class has poor prognosis, findings that have been repeatedly reproduced [1921].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 In our cohort, patients presented with a mean eGFR value of 16.3 ml/min per 1.73 m 2 , similar to the values reported in other smaller cohorts. 9,10 The presence of MPO-ANCA (versus PR3-ANCA) has previously been reported as a determinant of renal outcome, 5,50,51 but multivariable modeling did not identify it as a risk factor for the development of severe renal disease in our cohort. Moreover, we showed that the presence of classic cardiovascular risk factors and increased age appear to aggravate the susceptibility of the kidney for severe renal disease in ANCA-associated GN.…”
Section: Discussionmentioning
confidence: 61%
“…We have also found that patients with anti‐MPO vasculitis and a recurrent ANCA pattern were more prone to worsening renal function. It is generally accepted that patients with anti‐MPO antibodies have a worse renal prognosis and a higher risk of progression to ESRD than patients with anti‐PR3 antibodies [24,27–33], although not all studies have confirmed this association [34–36]. Patients with anti‐MPO antibodies usually have more glomerulosclerosis and interstitial fibrosis on renal biopsies than patients with anti‐PR3 antibodies [30,32,34,36].…”
Section: Discussionmentioning
confidence: 99%